Numerical analysis of the transient turbulent flow in a fuel oil storage tank - Vardar, N (PERGAMON-ELSEVIER SCIENCE LTD, 2003)
The filling process of a fuel oil storage tank containing a higher temperature fuel oil is numerically analysed. A k-epsilon model, which is developed by some modifications to those existing in the literature, is employed in order to take into account the turbulent effect for low-Re flow phenomena. A transient stream function-vorticity formulation is used for predicting streamlines and temperature distribution. The streamlines, the isotherms and the transient average temperature variations are presented for three different inflow velocities and for three different cases of heating. (C) 2003 Elsevier Science Ltd. All rights reserved.
Keywords: STRATIFIED THERMAL STORAGE; NATURAL-CONVECTION; TEMPERATURE; PREDICTION; PETROLEUM; Thermodynamics; Engineering; Mechanics